Efficacy and safety of tedizolid for the treatment of ventilated gram-positive hospital-acquired or ventilator-associated bacterial pneumonia in Japanese patients: Results from a subgroup analysis of a phase 3, randomized, double-blind study comparing tedizolid and linezolid. Issue 9 (September 2022) - Mikamo, Hiroshige; Nagashima, Makoto; Kusachi, Shinya; Fujimi, Satoshi; Oshima, Nobuyuki; De Anda, Carisa; Takase, Akiko
Abstract: Introduction: The results from the phase 3 study that evaluated the efficacy and safety of tedizolid phosphate, an oxazolidinone drug, for the treatment of gram-positive ventilated hospital-acquired bacterial pneumonia (vHABP)/ventilator-associated bacterial pneumonia (VABP) compared with linezolid (VITAL study), have been previously reported. We conducted a subgroup analysis to report the data obtained from Japanese patients enrolled in this study. Methods: Patients aged ≥18 years with vHABP/VABP likely to be caused by gram-positive cocci were randomized 1:1 to tedizolid phosphate 200 mg once daily for 7 days or linezolid 600 mg twice daily for 10 days. In both treatment groups, patients with concurrent gram-positive bacteremia were treated for 14 days. Primary efficacy endpoints were day 28 all-cause mortality (ACM) and investigator-assessed clinical response at test-of-cure (TOC) in the intention-to-treat population. Safety outcomes included assessment of treatment-emergent adverse events. Results: Fifty-three Japanese patients were randomized at received study drug (tedizolid, n = 28; linezolid, n = 25). Demographics and characteristics were generally similar between treatment groups. Rates of day 28 ACM were 10.7% and 20.0% with tedizolid and linezolid, respectively (difference, 9.3%; 95% CI, −10.1 to 28.7). Rates of investigator-assessed clinical cure at TOC were 78.6% and 72.0% with tedizolid and linezolid, respectively (difference, 6.6%; 95% CI, −16.7 to 29.8). Tedizolid phosphate was generally well tolerated and no new safety concerns were observed in the Japanese subgroup. Conclusion: The results from this subgroup analysis suggest generally favorable efficacy and safety of tedizolid in adult Japanese patients with vHABP/VABP. (ClinicalTrials.gov identifier: NCT02019420).